The impact of perceived quality, advertising quality, and herding effect on purchase intention: Moderation effect of age - Lu, Xi; Yin, Yitong; Gao, Ruizhe; Sari, Nasi (Journal of Asian Business Strategy, 2024)
In recent years, with the rapid development of technology, the development trend of online game industry is good. This paper focuses on the online gaming industry and discusses the factors that affect the willingness of Chinese college students to purchase products on gaming platforms. This paper selects consumer perception quality, advertising quality, and herd effect on game platforms as the main research variables through literature review. This paper introduces age as a moderating effect, investigate the moderating mechanism of age groups on the three main research variables. This paper found that both perceived quality and herd effect have a positive impact on consumer purchase intention, while age has a positive moderating effect on herd effect and the combined variables of perceived quality and herd effect. However, advertising quality has no significant impact on consumers’ purchase intention, and the moderating effect of age on the impact of advertising quality on purchase intention is not significant. The paper falls into six parts. Firstly, it introduces the background, purpose, significance, conceptual framework, and contribution. Secondly, it introduces the literature review and assumptions. Thirdly, it presents the methodology. Fourth, it introduces the discovery of the study. Fifth, it indicates the discussion and implication. Sixth, it concludes the main points. The innovation lies in the following points. Firstly, this paper focuses on the consumption behavior of Chinese college students in online games. Secondly, this paper incorporates multiple variables mentioned in existing literature into the research mode. Thirdly, this paper introduces age groups as moderating variables.